2008
DOI: 10.1158/1535-7163.mct-07-2388
|View full text |Cite
|
Sign up to set email alerts
|

Eps8 decreases chemosensitivity and affects survival of cervical cancer patients

Abstract: The oncoprotein Eps8 facilitates proliferation in fibroblasts and colon cancer cells. However, its role in human cervical cancer is unclear. By immunohistochemical staining and Western blotting, aberrant Eps8 expression was observed in cervical carcinoma compared with normal cervical epithelial cells. Clinicopathologic analysis of 45 patients indicated that Eps8 expression was associated with parametrium invasion and lymph node metastasis, two major poor prognostic factors for early-stage cervical cancer. Kapl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 41 publications
4
50
1
Order By: Relevance
“…Reduced activity of Src and FAK in Eps8-attenuated RAW cells suggested that Eps8 might directly regulate the activity of both kinases as reported previously (22,42). Given that cytochalasin B exerted no effect on the activity of Src and FAK but significantly inhibited LPS-elicited Eps8 expression as well as phagocytosis of GFP-E. coli (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…Reduced activity of Src and FAK in Eps8-attenuated RAW cells suggested that Eps8 might directly regulate the activity of both kinases as reported previously (22,42). Given that cytochalasin B exerted no effect on the activity of Src and FAK but significantly inhibited LPS-elicited Eps8 expression as well as phagocytosis of GFP-E. coli (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…Overexpression of Eps8 conferred the ability of fibroblasts to form focus in culture dish and grow tumor in mice (Maa et al, 2001), corroborating the oncogenic potential of Eps8. In agreement, Eps8 attenua tion retarded cellular growth in IV5 cells (Leu et al, 2004) and human cancer cells (Maa et al, 2007;Chen et al, 2008;Xu et al, 2009). Remarkably, Eps8 is also a prognostic factor for cervical cancer.…”
Section: Introductionsupporting
confidence: 58%
“…Unlike the involvement of Eps8 in cytoskeletal reorganization is gradually disclosed, the implication of Eps8 in tumorigenesis is well established. Elevated expression of Eps8 was observed in v-Src transformed (IV5) cells (Gallo et al, 1997;Maa et al, 1999), and in a variety of human tumors including colorectal (Maa et al, 2007), cervical (Chen et al, 2008), pituitary (Xu et al, 2009) and oral cancers (Yap et al, 2009). Overexpression of Eps8 conferred the ability of fibroblasts to form focus in culture dish and grow tumor in mice (Maa et al, 2001), corroborating the oncogenic potential of Eps8.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Eps8 enhances EGF-dependent mitogenic signals and leads to malignant transformation (1,20). Eps8 increases cell growth and motility, by the up-regulation of FOXM1, FAK, MMP-9, ERK, Akt, cyclins D1, D3, and E, the down-regulation of P53 and p21Waf1/Cip1 in squamous cell carcinoma, pancreatic cancer, cervical cancer, colon cancer, pituitary tumors and esophageal carcinomas (4,5,(21)(22)(23)(24)(25)(26). Eps8 is an important signal molecule, we demonstrated here that ITSN2 and Eps8 interact in vivo, and the interaction between both proteins results in the decrease of Eps8 proteins.…”
Section: Introductionmentioning
confidence: 99%